Highly imbalanced fault diagnosis of mechanical systems based on wavelet packet distortion and convolutional neural networks. (January 2022) - Zhao, Minghang; Fu, Xuyun; Zhang, Yongjian; Meng, Linghui; Tang, Baoping
Abstract: The healthy operations of mechanical systems are crucially important for ensuring human safety and economic benefits, so that there is a high demand on the automatic fault diagnosis techniques. However, the number of available faulty samples of mechanical systems is often far less than healthy samples, and thereby the traditional data-driven methods often suffer a high rate of misdiagnosis. In this paper, a new fault diagnosis method is developed on the basis of wavelet packet distortion and convolutional neural networks. First, wavelet packet distortion means that wavelet packet coefficients are distorted to augment fault samples, in order to achieve the equilibrium between healthy and faulty classes. Second, a convolutional neural network-based classification model is trained using the balanced training dataset. Third, the trained model is applied to classify the testing samples. Finally, the efficacy of this developed method in imbalanced fault diagnosis of mechanical systems is demonstrated through a number of experiments.